Carbonic Maceration Fermentation Process on Arabica Arjuno Yellow Caturra Coffee: Effect of CO2 Injection and Roasting Level on Physiochemistry and Sensory Characteristics - Hanif, Muhamad Ibnu; Widjanarko, Simon Bambang; Maligan, Jaya Mahar (Jurnal Pangan dan Agroindustri, 2025)
Arabica Yellow Caturra, a newly cultivated coffee variety in Indonesia, exhibits an unbalanced flavor profile that diminishes its consumer appeal. To enhance its competitiveness in both domestic and international markets, appropriate post-harvest processing techniques are essential. This study investigated the impact of carbonic maceration - a fermentation method involving CO₂ gas injection on the physicochemical and sensory properties of coffee powder. Analyses included physicochemical properties (colour, moisture, ash content, pH, caffeine, total acidity) and sensory attributes. Results indicated that CO₂ injection intensity significantly influenced colour characteristics, pH levels, and caffeine content (p< 0.05). In contrast, the roasting level significantly affected colour, moisture content, ash content, caffeine concentration, total acidity, and the sensory attributes of body and uniformity (p< 0.05). The optimal treatment, identified by the highest Cupping Test score (81.88), involved CO₂ injection at the initial stage of fermentation combined with light roasting.